Wnt signaling is required for early development of zebrafish swimbladder. - Ao Yin; Svitlana Korzh; Cecilia L Winata; Vladimir Korzh; Zhiyuan Gong (PLoS ONE)
Background Wnt signaling plays critical roles in mammalian lung development. However, Wnt signaling in the development of the zebrafish swimbladder, which is considered as a counterpart of mammalian lungs, have not been explored. To investigate the potential conservation of signaling events in early development of the lung and swimbladder, we wish to address the question whether Wnt signaling plays a role in swimbladder development. Methodology/principal findings For analysis of zebrafish swimbladder development, we first identified, by whole-mount in situ hybridization (WISH), has2 as a mesenchymal marker, sox2 as the earliest epithelial marker, as well as hprt1l and elovl1a as the earliest mesothelial markers. We also demonstrated that genes encoding Wnt signaling members Wnt5b, Fz2, Fz7b, Lef1, Tcf3 were expressed in different layers of swimbladder. Then we utilized the heat-shock inducible transgenic lines hs:Dkk1-GFP and hs:ΔTcf-GFP to temporarily block canonical Wnt signaling. Inhibition of canonical Wnt signaling at various time points disturbed precursor cells specification, organization, anterioposterior patterning, and smooth muscle differentiation in all three tissue layers of swimbladder. These observations were also confirmed by using a chemical inhibitor (IWR-1) of Wnt signaling. In addition, we found that Hedgehog (Hh) signaling was activated by canonical Wnt signaling and imposed a negative feedback on the latter. Significance/conclusion We first provided a new set of gene markers for the three tissue layers of swimbladder in zebrafish and demonstrated the expression of several key genes of Wnt signaling pathway in developing swimbladder. Our functional analysis data indicated that Wnt/β-catenin signaling is required for swimbladder early development and we also provided evidence for the crosstalk between Wnt and Hh signaling in early swimbladder development.